“I Can Teach With My Videos”: How Do Teachers Teach English to Young Learners in a Technology-Limited Environment? - Astutik, Yuli; Setiawan, Slamet; Anam, Syafi’ul; Suhartono, Suhartono (International Journal of Learning, Teaching and Educational Research, 2022)
To ensure that learning continues during the Covid-19 pandemic, educators must understand pedagogical and content knowledge through the integration of information and communication technology (ICT). An example is English teachers at elementary schools in Indonesia making videos to help young learners learn English remotely. This paper aims to find out how teachers maximize student learning from their videos in a technology-limited environment and how teachers integrate their role as facilitators into their videos. We gathered data by conducting observations of three English teachers for four months during the odd semester of the 2021–2022 academic year and interviews with the participants. The research findings indicated that participants implemented a cognitive load aspect that makes it easier for young learners to see real examples of objects, even if only on video, thereby reducing excessive cognitive load. In addition, the participants implemented the student engagement aspect, which reduces the intrinsic load and makes the text in the video more meaningful. A third aspect implemented was active learning, which serves to help students and teachers develop strong feelings of social cooperation. Moreover, participants integrated their role as facilitators in educational videos by using an information guide and by being friendly inquirers to their students. The findings imply that if packaged properly, teacher videos can be one of the learning techniques that teachers and students can use in any situation. Furthermore, unlike in offline learning, students can replay teaching videos to aid their learning process, without having to ask the teacher to repeat the explanation. https://doi.org/10.26803/ijlter.21.7.9